5x+55=9x-9

Simple and best practice solution for 5x+55=9x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+55=9x-9 equation:


Simplifying
5x + 55 = 9x + -9

Reorder the terms:
55 + 5x = 9x + -9

Reorder the terms:
55 + 5x = -9 + 9x

Solving
55 + 5x = -9 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
55 + 5x + -9x = -9 + 9x + -9x

Combine like terms: 5x + -9x = -4x
55 + -4x = -9 + 9x + -9x

Combine like terms: 9x + -9x = 0
55 + -4x = -9 + 0
55 + -4x = -9

Add '-55' to each side of the equation.
55 + -55 + -4x = -9 + -55

Combine like terms: 55 + -55 = 0
0 + -4x = -9 + -55
-4x = -9 + -55

Combine like terms: -9 + -55 = -64
-4x = -64

Divide each side by '-4'.
x = 16

Simplifying
x = 16

See similar equations:

| 2(3a+9)=20 | | 26p-4-11p=15p+6 | | 8x-4=4x+44 | | -6(4x+7)=78 | | -7p-39=5(-5p+3) | | -8(2x-2)=128 | | -14+4x-2x=30 | | P=A-ArT | | X^2+4y^2+6x+16y=11 | | 3x^26y-24=0 | | 10(9-x)= | | 35-(2c+3)=2(c-6)+c | | -7p-39=5(-5p+30) | | 3y+6x=360 | | 10x^2-17x+34=7x^2-26x+28 | | -15+-14e=-33 | | -13-8j=-5 | | 9m+6=96# | | 4b+6=-22 | | 4(p+5)=2 | | -43=13p-65 | | 0=x^4+4x^2-32 | | y=(-8)(1) | | (X+10)(x)=144 | | 21-4j=13 | | 11-3*3-1= | | -2(x+y)+9=1 | | -7=6m-7m | | 6(X-1)=2x+6 | | (x-2)*(x+3)=x*x-8 | | 17d-5=3d | | y=-16t^2+468 |

Equations solver categories